Unraveling the biology, effects and management methods of Sclerotium rolfsii infection in plants for sustainable agriculture - Okon Godwin Okon; Yakubu Ismaila Uwaidem; Abdelhak Rhouma; Ukponobong Effiong Antia; Joseph Etim Okon; Bright Frank Archibong (European Journal of Biological Research)
Sclerotium rolfsii is an economically important soil-borne fungal pathogen that affects various crops worldwide, causing diseases such as blight, collar rot, crown rot, damping-off, Sclerotium wilt, and stem rot. It primarily attacks stems but can also infect roots, fruits, petioles, leaves, and flowers under favorable conditions. Initial symptoms include yellowing and wilting of leaves, followed by the appearance of white, fluffy mycelium on infected tissues and soil. The fungus forms round, white sclerotia that mature into dark brown or black structures resembling mustard seeds. These sclerotia enable S. rolfsii to survive unfavorable conditions for up to seven years in soil. The fungus has an extensive host range of over 500 species across 100 plant families. S. rolfsii thrives at or near the soil line. Before penetrating host tissue, it produces a considerable mass of mycelium on the plant surface over 2 to 10 days. The pathogen secretes enzymes that degrade the host's outer cell layer, leading to tissue decay, further mycelium production, and sclerotia formation. Managing S. rolfsii is challenging due to its broad host range and persistent sclerotia. Biological control methods have been explored, focusing on bacterial and fungal antagonists. Pseudomonas and Bacillus species have been studied for their ability to inhibit hyphal growth and reduce sclerotia germination. Additionally, antagonistic fungi, including Gliocladium virens, G. roseum, Glomus fascicatum, Penicillium pinophilum, Gigaspora margarita, and various arbuscular mycorrhizal fungi, have shown promise in suppressing S. rolfsii.